The role of CBCT in diagnosing and managing cleft lip and palate - Anjani, Khamila Gayatri; Rachmawati, Ika; Epsilawati, Lusi; Pramanik, Farina (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2025)
Objectives: Cleft lip and palate (CLP) are one of the most common types of congenital maxillofacial lesions. Cleft lip and palate patients often deal withspeech, masticatory and hearing problems, dental and craniofacial anomalies, and psychosocial issue. The aim of this study is to determine the role of cone beam computed tomography (CBCT) in diagnosing CLP. Case Report: A 25-year-old female was referred to dentomaxilllofacial radiology department in Universitas Padjadjaran Dental Hospital for a CBCT examination of a cleft palate. Three-dimensional image analysis provides superior and more detailed information compared with conventional plain two-dimensional (2D) radiography, with the added benefit of 3D printing for preoperative treatment planning and regenerative therapy. The result showed a radiolucent area between teeth 21 and 23, agenese teeth 22. These findings led to cleft palate unilateral complete at sinistra region. CBCT imaging provides a detailed picture of the cleft in three dimensions view that can helps for determining the treatment plan based on the classification of cleft lip and palate. Conclusion: Available evidence implies that 3D imaging methods not only can be used for documentation of CLP patients, but also can determining the treatment plan. 3D CBCT radiograph are more informative than conventional 2D.